Towards a Sustainable Land Administration and Management System in Myanmar - World Bank Group (World Bank, Washington, DC, 2018)
Key elements for effective policy and regulatory framework on land that should be developed are:Ensuring proper human and financial resources are dedicated to implementation of the NationalLand Use Policy and functioning of the National Land Use Council, Developing an effective land governance system based on the current legal framework while drafting of new laws tocover: (i) protections for customary user'’ tenure rights; (ii) the promotion of diverse agricultural practices such as livestock breeding and aquaculture; (iii) directing land allocation policies to improve land access for marginal farmers and landless households; and (iv) establishing programs such as a model land administration offices with enhanced service delivery. Amendment of current land laws to expand the roles of farmers and community members in land use decision making. The promotion of the revised community forest instruction, which broadly reinterpreted the forest law to remove restrictions on shifting cultivation to protect customary land rights and to protect in community decision making on land use, allocation and possible conversion to commercial use; including promotion of community forests and commercialization for inclusive economic growth at the grassroots level.